Polycyclic Aromatic Hydrocarbon Degradation in the Sea-Surface Microlayer at Coastal Antarctica - Martinez-Varela, Alícia; Casas, Gemma; Berrojalbiz, Naiara; Piña, Benjamin; Dachs, Jordi; Vila-Costa, Maria (Frontiers in Microbiology, 2022)
As much as 400 Tg of carbon from airborne semivolatile aromatic hydrocarbons are deposited to the oceans every year, the largest identified source of anthropogenic organic carbon to the ocean. Microbial degradation is a key sink of these pollutants in surface waters, but has received little attention in polar environments. We have challenged Antarctic microbial communities from the sea-surface microlayer (SML) and the sub-surface layer (SSL) to polycyclic aromatic hydrocarbons (PAHs) at environmentally relevant concentrations. PAHs degradation as well as the microbial responses at compositional and functional level were assessed. Evidence for faster removal rates were observed in the SML, with rates 2.6-fold higher than in the SSL. In the SML, the highest removal rates were observed for the more hydrophobic, and particle-bound PAHs. After 24 hours of PAHs exposure, particle-associated bacteria in the SML showed the highest number of significant changes in their composition. These included significant enrichments of several hydrocarbonoclastic bacteria, especially the fast-growing genera Pseudoalteromonas, which increased their relative abundances by 8-fold. Simultaneous metatranscriptomic analysis showed that the free living fraction of SML was the most active fraction, especially for members of the order Alteromonadales, that includes Pseudoalteromonas. Their key role on PAHs biodegradation in polar environments should be elucidated in further studies. This study highlights the relevant role of bacterial populations inhabiting the sea surface microlayer, especially the particle-associated habitat, as relevant bioreactors for removal of aromatic hydrocarbons in the oceans.